Antimicrobial activity of marine bacteria isolated from Gulf of Mexico - Matos, Adriana (2010)
Currently there is a need for new antibiotics with an alternative mode of action and new chemical structures. Bacterial pathogens are gradually becoming more resistant to conventional antibiotics, generating an emergence of infectious diseases and they are becoming a great problem in the field of public health. In this study, seven different isolated bacteria were obtained from offshore seawater and sediment of the Gulf of Mexico from Campeche, Mexico. They were substance producers which inhibit growth of human pathogens like Staphylococcus aureus and Pseudomonas aeruginosa and one of them was a polymer producer on peptone and glucose culture. They were characterized phenotipically by means of morphological techniques and physiologically by conventional tests. Four of them were Gram-positive bacteria and the Scanning Electron Microscope analysis revealed their size between 0.6 - 1.5 µm. One of seven marine strains, Gram negative, yellow pigmented, slightly curved rods, was identified as Pseudoalteromonas sp. on the analysis of the gen16S rRNA sequence.